2016
DOI: 10.1093/ndt/gfw053
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibitor/angiotensin receptor blocker use and cardiovascular outcomes in patients initiating peritoneal dialysis

Abstract: A B S T R A C TBackground: Data on the effectiveness of angiotensinconverting enzyme inhibitors (ACEIs) and angiotensin II receptor blockers (ARBs) in reducing cardiovascular (CV) risk in patients undergoing peritoneal dialysis (PD) are limited. We investigated the association between ACEI/ARB use and CV outcomes in patients initiating PD. Methods: In this observational cohort study, we identified from the United States Renal Data System all adult patients who initiated PD from 2007 to 2011 and participated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
1
12
1
Order By: Relevance
“…ACEI. Previous studies have shown an association between ACEI or ARB ( vs. no use) and a reduction in CV events in patients on PD,[5,21] but, to our knowledge, ours is the first to compare the two classes of medications in PD patients.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…ACEI. Previous studies have shown an association between ACEI or ARB ( vs. no use) and a reduction in CV events in patients on PD,[5,21] but, to our knowledge, ours is the first to compare the two classes of medications in PD patients.…”
Section: Discussionmentioning
confidence: 92%
“…[1] While angiotensin-converting enzyme inhibitors (ACEI) and angiotensin-II receptor blockers (ARB) are recommended for the reduction of CV events for certain populations without ESKD, there is evidence that these agents may reduce the risk of CV events in patients on maintenance dialysis as well. [29] In fact, guidelines recommend the use of either ACEI or ARB as a first-line anti-hypertensive for those with diabetic nephropathy with proteinuria and for patients on dialysis with residual kidney function, and suggest use of either ACEI or ARB for normotensive patients on peritoneal dialysis (PD) with residual kidney function. [10,11]…”
Section: Introductionmentioning
confidence: 99%
“…The use of angiotensin converting enzyme inhibitors (ACEI), angiotensin II receptor blockers (ARB) and beta blockers (BB) should be considered in PD patients with LVH, dilated cardiomyopathy or systolic heart failure; when already receiving treatment with ACEI or ARB, consider adding a mineralocorticoid receptor antagonist (MRA) 114 . Observational studies showed that ACEI/ARB utilization is associated with a reduction in cardiovascular events, and cardiovascular and all-cause mortality, even after adjusting for other risk factors and patient characteristics 127,128 . Concerning the treatment with MRA, a randomized controlled trial (RCT) in PD showed that, when added to a ACEI or ARB, spironolactone significantly reduces the rate of progression in left ventricular mass index and improves ejection fraction for 24 months 129 .…”
Section: Left Ventricular Hypertrophy and Dysfunction |Heart Failurementioning
confidence: 99%
“…In view of these facts, the clinical question arose as to whether RASIs preserve the RRF of PD patients. Several clinical studies were performed to estimate the effect of RASIs on RRF of PD patients [10][11][12][13][14][15][16][17][18][19][20][21][22], including both randomized controlled trials (RCTs) and non-RCTs, with conflicting results.…”
Section: Introductionmentioning
confidence: 99%